Effect of Eight-Week Underwater Trampoline Exercise on Postural Control, Strength, And Quality of Life in Middle-Aged Women - Elham Baqlaei; Morteza Sadeghi (Shiraz University of Medical Sciences, 2018)
Background: The effects of aquatic exercises on strength and balance are still controversial, nevertheless an attempt has been made to investigate the effect of underwater trampoline exercise, in comparison with traditional aquatic exercise, on strength, balance, and quality of life in middle-aged women Methods: A total of 26 middle-aged women participated in this study. The participants were randomly allocated into two groups, i.e. underwater trampoline exercise (age: 44.8±10.3yr, height: 1.62±0.6 m, weight: 76.2±8.6 kg) and traditional aquatic exercise (age: 45.7±8.8yr, height: 1.58±0.5 m, weight: 71.8±8.8 kg), using a matching method. Static balance (by stork test), strength (by dynamometer), and quality of life (by SF 36 questionnaire) data were collected before and after applying an 8-week exercise regime (three sessions per week, each session of 30-45 minutes duration). Finally, the data was analyzed by repeated measures ANOVA using SPSS software (Version 21) (P<0.05). Results: The data analysis showed a significant interaction (P<0.05) in regard to higher mean value of criteria in the underwater trampoline group, however the values of hamstring strength and quality of life between the two groups were not significantly different. Conclusion: The current study showed that underwater trampoline exercises can well affect the balance and strength of the users. The underwater trampoline group showed better progress in terms of the mentioned criteria. Therefore, it can be concluded that the underwater trampoline device can create a unique aquatic environment for enhanced therapeutic treatment and musculoskeletal rehabilitation.